Analysis of Perceptions and Preferences of Muslim and Non-Muslim Communities Towards Providing Sharia Labels at NTB Shariah Bank an Lombok Island (Study in Mataram City) - Putri, Dwika Ambar; Yusuf, Muhammad; Yusuf, M. (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2024)
This research aims to reveal what the perceptions and preferences of Muslim and non-Muslim communities are regarding giving sharia labels to NTB sharia banks on the study island of Lombok, Mataram City . This research uses a quantitative approach with the research object being Muslim communities and non-Muslim communities in the city of Mataram. The choice of Muslim and non-Muslim communities in the city of Mataram as the research setting was based on the issue of how they perceive sharia labeling at NTB sharia banks considering that NTB sharia banks have just converted in 2018 (from conventional to sharia banks). The data collection method was carried out by means of interviews and documentation, while data analysis used descriptive qualitative data analysis. The results of this research show that Muslim and non-Muslim communities in the city of Mataram agree with the government's policy of converting NTB banks to sharia which is considered to be a new idea in developing the economy of NTB province.